Zingerone Targets Status Epilepticus by Blocking Hippocampal Neurodegeneration via Regulation of Redox Imbalance, Inflammation and Apoptosis - Summya Rashid; Adil Farooq Wali; Shahzada Mudasir Rashid; Rana M. Alsaffar; Ajaz Ahmad; Basit L. Jan; Bilal Ahmad Paray; Saeed M. A. Alqahtani; Azher Arafah; Muneeb U. Rehman (Pharmaceuticals, 2021)
Epilepsy is an intricate neurological disease where the neurons are severely affected, leading to the mortality of millions worldwide. Status epilepticus (SE), induced by lithium chloride (LiCl) and pilocarpine, is the most accepted model for epilepsy. The current work aims to unravel the mechanisms underlying the anti-epileptic efficacy of zingerone (an active ingredient of ginger), which has beneficial pharmacological activities on seizure-induced behavioral, histological, neurochemical, and molecular patterns in mice. Zingerone restored cognitive function by diminishing seizure activity, escape latency, and subsequent hippocampal damage manifested in histology. Seizures are associated with local inflammation, redox imbalance, and neural loss, confirmed by the present study of SE, and was attenuated by zingerone treatment. Nuclear factor-kappa B and its downstream signaling molecules (TNF-α, IL-1β, IL-6, NO, MPO) were activated in the LiCl-and-pilocarpine-induced group leading to inflammatory signaling, which was substantially ameliorated by zingerone treatment. The intrinsic apoptotic process was triggered subsequent to SE, as demonstrated by augmentation of cleaved caspase-3, downregulation of Bcl-2. However, zingerone treatment downregulated caspase-3 and upregulated Bcl-2, increasing cell survival and decreasing hippocampal neural death, deciphering involvement of apoptosis in SE. Therefore, zingerone plays an essential role in neuroprotection, probably by precluding oxidative stress, inflammation, and obstructing the mitochondrial pathway of apoptosis.